Use of patient-relevant outcome measures to assess the long-term effects of care bundles in the ICU: a scoping review protocol. Issue 2 (15th February 2022) - Paul, Nicolas; Knauthe, Anna-Christina; Ribet Buse, Elena; Nothacker, Monika; Weiss, Björn; Spies, Claudia
Abstract : Introduction: There is only moderate adherence to evidence-based practice in critical care. Care bundles can be used to increase adherence to best clinical practice. Components of bundle interventions, bundle implementation rates, barriers and facilitators of bundle implementation, and the effect of care bundles on short-term patient outcomes such as intensive care unit (ICU) mortality all appear to be regularly studied. However, over the last years, critical care research has turned towards long-term patient-relevant outcomes after discharge from the ICU. To our knowledge, there is no systematic overview on the long-term effect of care bundle implementation on patient-relevant outcomes. We present a protocol for a scoping review of the available literature on the effect of the implementation of care bundles in the ICU on long-term patient-relevant outcomes. Methods and analysis: This scoping review will adhere to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines and the Arksey and O'Malley framework. The recommendations of the Joanna Briggs Institute for Scoping Reviews will also be followed. A systematic literature research will be performed using electronic databases (MEDLINE, EMBASE, CINAHL, PsycINFO, Web of Science, CDSR and CENTRAL). A preliminary search has been conducted on 1 September 2021, yielding 1929 entries. The main search, data extraction and charting has not been started yet. This scoping review will provide an overview of the long-term patient-relevant outcomes that have been used to assess the implementation of care bundles in the ICU. It will be the first study to summarise the long-term impact of care bundles for critically ill patients and identify research gaps to inform future research. Ethics and dissemination: Due to the utilisation of already published primary studies, ethical approval is dispensable. Results of this work will be published in a peer-reviewed journal.